2013
DOI: 10.1590/0103-6440201302152
|View full text |Cite
|
Sign up to set email alerts
|

Preferences on Vital and Nonvital Tooth Bleaching: A Survey Among Dentists from a City of Southern Brazil

Abstract: This study evaluated the preferences of general dentists regarding vital and nonvital tooth bleaching therapies and investigated whether the time of clinical practice and postgraduate training influence these options. A cross-sectional study was conducted using a questionnaire with closed questions applied to dentists (n=276) of a mid-sized city of the southern Brazil (Pelotas, RS). Information was collected regarding sociodemographic variables, level of specialization and time since graduation. In addition, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
2
39
3
Order By: Relevance
“…In the present study, the same concentration of hydrogen peroxide was used, but in different application methods: HP gel and whitening strips. Whitening strips are an OTC method easy to use and less expensive than at-home or in-office bleaching methods, presenting some efficacy in tooth color recovery (21,22) and these are some of the reasons for their growing popularity (4). Few studies have investigated enamel microhardness after the use of hydrogen peroxide strips and the results demonstrated no deleterious effect on the enamel microhardness (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the same concentration of hydrogen peroxide was used, but in different application methods: HP gel and whitening strips. Whitening strips are an OTC method easy to use and less expensive than at-home or in-office bleaching methods, presenting some efficacy in tooth color recovery (21,22) and these are some of the reasons for their growing popularity (4). Few studies have investigated enamel microhardness after the use of hydrogen peroxide strips and the results demonstrated no deleterious effect on the enamel microhardness (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Tooth bleaching has become a popular treatment, with a large variability of commercial presentations that may be applied in the dental office, at-home under the supervision of the dentist or using over-the-counter (OTC) products without professional supervision (3). At-home bleaching treatment is the preferred treatment protocol for vital teeth according to the Brazilian dentists, using low concentration gels with mouthguards, while OTC products are used/ recommended by 5% of these dentists (4).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent questionnaire-based survey conducted in the southern of Brazil, at-home bleaching was broadly preferred (78.1 %) for vital tooth bleaching compared with in-office therapy (21.9 %) [7]. This trend seems to occur worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation was carried out using a questionnaire whose content was confirmed by pediatric dentists and endodontists. Previous studies have shown that post-graduation training affect the adhesive system selection, the choice of vital bleaching treatment, application of rubber dam for composite restoration as well as the choice of post for endodontically treated teeth (Demarco et al 2013a;2013b;Nascimento et al 2013). …”
Section: Discussionmentioning
confidence: 99%